2022
DOI: 10.21037/tau-22-501
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the role of glucocorticoid receptors in prostate cancer: developments in last 5 years

Abstract: Background and Objective: Glucocorticoids, secreted from the adrenal gland, are commonly used in the treatment of castration-resistant prostate cancer (CRPC) because of their anti-inflammatory and antitoxic effects. However, glucocorticoids have been reported to have the opposite effects within the course of treatment. Many studies have shown that glucocorticoid receptors (GRs) are involved in the establishment of a dominant population of androgen-independent malignant cells, which may result in CRPC. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Data from pre-clinical and clinical studies suggest that corticosteroids can induce treatment resistance in solid tumors [ 19 ]. In recent years, it has been established that glucocorticoid receptors (GRs) may be involved in the development of castration-resistant prostate cancer (CRPC) [ 20 , 21 ]. The upregulation of the GR may drive tumor proliferation and possibly lead to resistance to antiandrogen therapies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from pre-clinical and clinical studies suggest that corticosteroids can induce treatment resistance in solid tumors [ 19 ]. In recent years, it has been established that glucocorticoid receptors (GRs) may be involved in the development of castration-resistant prostate cancer (CRPC) [ 20 , 21 ]. The upregulation of the GR may drive tumor proliferation and possibly lead to resistance to antiandrogen therapies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the combination of AR and EZH2 inhibits GR transcriptio [ 15 ], the expression level of GR in prostate cancer tissues is relatively low initially, while the effect of AR is inhibited during ADT treatment, and the expression of GR graduated increased. The combination of GR and GRE activates AR downstream genes through the bypass pathway and promotes the progression of prostate cancer [ 14 , 16 ]. These results indicate that there is an extremely complex relationship between GR and AR, and the interaction between them affects the occurrence and development of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained ER+/Her2− breast cancer data from METABRIC ( https://www.cbioportal.org/study/summary?id=brca_metabric ), used the impute package for data cleaning and gap-filling, merged the NR3C1 [ NR3C1 encodes GRs, is located on chromosome 5 (region 5q31.3) ( 25 )] gene expression data with ER+/Her2− breast cancer patient survival data, and obtained 1,475 gene identity document (ID) numbers. We also obtained a preprocessed dataset (GSE139870) from the GEO ( https://www.ncbi.nlm.nih.gov/geo/ ) database, which was established based on the anti-proliferative transcriptional effects of medroxyprogesterone acetate in ER+ breast cancer cells predominantly mediated by the progesterone receptor (HG-U133A) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%